Evaluation of intelligent search agents for the World Wide Web - Lee, Chye Seng. (2011)
An Intelligent Search Agent is a computer program that is capable of performing on-line and off-line searching on behalf of Internet users. The software is able to launch smart agents that can traverse the World Wide Web and even exchange information with other agents in retrieving information. The aim of this research is to evaluate how effective these Intelligent Search Agents are in retrieving relevant information from the World Wide Web. To help readers better understand this new technology, a brief description of their definition, types, attributes and capabilities is included. A literature review is carried out to gather more information on the search agents currently available and the latest development of this Internet technology. At present, mere are many different types of Intelligent Agents available in the IT industry and they serve specific purposes in their usage. This research focuses on those search agents that can assist us in information retrieval on the World Wide Web. Five search agents are evaluated, with due consideration to user profiling, usability, relevance, cost, adaptability and flexibility.